1996
DOI: 10.1095/biolreprod55.3.519
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Decidual Cell Reaction by Androgens in the Mouse1

Abstract: In the mouse, estrogen and progesterone are required to prime the uterus for decidual cell reaction (DCR) in response to an intraluminal stimulus and, once DCR is induced, progesterone is required to maintain DCR. However, some evidence indicates that certain nonprogestational steroid hormones may also be involved in regulating DCR. The present study determined whether androgen plays any role in DCR. Adult CD1 mice were ovariectomized and treated with a regimen of estradiol and progesterone to prime the uterus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Consistent with the roles for exogenous androgens described in human ESCs, in a murine decidualisation model, mice induced to decidualise in the presence of either testosterone or DHT exhibit enhanced responses to decidualisation characterised by increasing deciduoma weight and induction of alkaline phosphatase activity, a marker or decidualisation (Zhang & Croy 1996). Notably, these effects were reported to be reversed by co-treatment with the AR antagonist hydroxyflutamide consistent with an AR-dependent impact on decidualisation (Zhang & Croy 1996). Thus, evidence from studies directly manipulating AR expression or activity from the addition of exogenous androgens in human and rodent models has demonstrated a role for androgens in the regulation of decidualisation.…”
Section: Decidualisationsupporting
confidence: 65%
See 1 more Smart Citation
“…Consistent with the roles for exogenous androgens described in human ESCs, in a murine decidualisation model, mice induced to decidualise in the presence of either testosterone or DHT exhibit enhanced responses to decidualisation characterised by increasing deciduoma weight and induction of alkaline phosphatase activity, a marker or decidualisation (Zhang & Croy 1996). Notably, these effects were reported to be reversed by co-treatment with the AR antagonist hydroxyflutamide consistent with an AR-dependent impact on decidualisation (Zhang & Croy 1996). Thus, evidence from studies directly manipulating AR expression or activity from the addition of exogenous androgens in human and rodent models has demonstrated a role for androgens in the regulation of decidualisation.…”
Section: Decidualisationsupporting
confidence: 65%
“…Kajihara and coworkers reported that treatment with DHT increases connexin-43 protein expression, a structural component of gap junctions, in decidualised human ESCs, which was accompanied by alteration of cellular ultrastructural features, including expansion of intracellular organelles and lipid droplet accumulation, all common features of decidualised cells (Kajihara et al 2014). Consistent with the roles for exogenous androgens described in human ESCs, in a murine decidualisation model, mice induced to decidualise in the presence of either testosterone or DHT exhibit enhanced responses to decidualisation characterised by increasing deciduoma weight and induction of alkaline phosphatase activity, a marker or decidualisation (Zhang & Croy 1996). Notably, these effects were reported to be reversed by co-treatment with the AR antagonist hydroxyflutamide consistent with an AR-dependent impact on decidualisation (Zhang & Croy 1996).…”
Section: Decidualisationsupporting
confidence: 59%
“…Furthermore, DHT was not capable of enhancing the P 4 -mediated increase in cad-11 expression in endometrial stromal cells. In addition, pharmacological doses of DHT were able to maintain, but not initiate, decidualization in the stromal cells of the mouse uterus (24). A, Autoradiograms of a Northern blot containing total RNA extracted from the treated endometrial stromal cells and probed for cad-11 (top) or 18S rRNA (bottom).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results demonstrate that androgens are unable to in-48, 72, or 96 h (lanes a-g) before being harvested for Northern or Western blot analysis. However, the actions of DHT on the rodent endometrium could be suppressed by the anti-progestin, RU486, suggesting that the actions of this androgen on the murine decidua were mediated by its ability to interact with the P 4 receptor (24). The absorbance values obtained from this study as well as those from two other studies (autoradiograms not shown) were standardized to the 0 h control and are represented (mean Ϯ SEM; n ϭ 3) in the bar graphs.…”
Section: Discussionmentioning
confidence: 99%
“…However, T and 5a-dihydrotestosterone are able to mimic the action of 17b-E 2 in initiating implantation in ovariectomized, P-treated mice (15,16). Although androgen does not prime the uterus for decidualization, it could maintain decidualization once decidualization occurs (17). However, female androgen receptor (AR)-deficient mice seem to be normal in implantation and decidualization except for longer estrous cycles and reduced fertility (18).…”
mentioning
confidence: 99%